The changes of electro dermal activity in the carrying of the coordination sensory-motor task - Benešová, Daniela; Rychtecký, Antonín; Štork, Milan (Acta Universitatis Carolinae. Kinanthropologica, 2009)
The aim of this pilot study was to monitor and assess the methodological presumptions for the diagnostic of the level of motor docility in individuals. The methods the testing of motor docility (teach ability) were carrying the unknown bimanual coordination task and the concurrent registration of the electro dermal activity of individuals. The registered changes of the arousal of subjects as changes in his/her individual’ psychic state were measured and expressed in the level of the electro dermal galvanic resistance. It was supposed, that the changes in the arousal of subject (electro dermal activity), registered during the carrying of the sensory-motor task would correspond to the course of running and final parameters in its performance (time and mistakes). Electro dermal activity (EDA) is the term for changes in the electrical conductance of the skin, including phasic changes that have been referred to as galvanic skin responses (GSR) that result from sympathetic neuronal activity. The Galvanic Skin Response (GSR) is one of several electro dermal responses (EDR). EDRs are changes in the electrical properties of a person’s skin caused by an interaction between environmental events and the individual’s psychical state. The human skin is a good conductor of electricity and when a weak electrical current is delivered to the skin, changes in the skin’s conduction of that signal can be measured. In this paper we would like to show on the relationship between the dynamics of EDR changes and the level of the motor docility of the subject, measured as the efficiency in carrying out the unknown bimanual – coordination task. The presented results which confirmed the mentioned above hypothesis should be consequently used in the creation and verification of the standard laboratory tests for the assessment of the subjects’ motor docility.
Keywords: motorické dovednosti; Motor Activity; Motor Skills; Learning; statistika jako téma; Skin Physiological Phenomena; konduktometrie; Signal Processing, Computer-Assisted; lidé; pilotní projekty; pohybová aktivita; Human Experimentation; Galvanic Skin Response; počítačové zpracování signálu; Conductometry; fyziologie kůže; financování organizované; Statistics as Topic; Humans; učení; experimenty na lidech; Pilot Projects; Financing, Organized; elektrofyziologické jevy; galvanická kožní odpověď; Electrophysiological Phenomena